Predicting receptive vocabulary change from childhood to adulthood: A birth cohort study - Armstrong, R.; Scott, J.; Copland, D.; McMahon, K.; Khan, A.; Najman, J.; Alati, Rosa; Arnott, W. (Elsevier Inc., 2016)
© 2016 Elsevier Inc. This study examined the parental and early childhood risk factors of different receptive vocabulary developmental profiles from childhood to adulthood. The sample (n = 1914), comprised of monolingual English speaking participants, from the Mater University of Queensland Study of Pregnancy (MUSP). Receptive vocabulary was measured using the Peabody Picture Vocabulary Test-Revised (PPVT-R) at the 5 and 21-year follow ups. Four vocabulary profiles were evident: persistently typical, persistently impaired, later onset of difficulties, and resolved delays. The presence of internalising behaviours at 5 years, lower paternal educational attainment, and maternal smoking during pregnancy were associated with later onset vocabulary impairment. These findings have clinical and educational implications for identifying children ‘at risk’ of later deterioration in language skills.